2018
DOI: 10.2147/cmar.s182652
|View full text |Cite
|
Sign up to set email alerts
|

Human epithelial growth factor receptor 2 in human salivary carcinoma ex pleomorphic adenoma: a potential therapeutic target

Abstract: BackgroundTo inhibit human epithelial growth factor receptor 2 (HER2) in salivary carcinoma ex pleomorphic adenoma (CXPA) and investigate the effects on tumor cell proliferation, cell cycle, and apoptosis. To assess the possibility of blocking HER2 to improve the malignant biological behavior of CXPA.Materials and methodsHER2 expression and amplification were examined using an immunofluorescence assay and fluorescence in situ hybridization in 2 CXPA cell lines (SM-AP1 and SM-AP4 cells). The effects on tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Pleomorphic adenoma (PA), one of the most common types of salivary neoplasms, typically occurs in the superficial lobe of the parotid gland and accounts for 60–70% of all parotid tumors [ 1 ]. Although initially benign, long-standing PA has the potential to transform into malignant pleomorphic adenoma (MPA) and subsequently infiltrate surrounding facial structures, which occurs in 6% of patients [ 2 , 3 ]. MPA can be further classified into three subtypes according to the depth of tumor infiltration beyond the capsule of the previous PA, namely, non-invasive, micro-invasive, and invasive malignant pleomorphic adenoma (IMPA) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pleomorphic adenoma (PA), one of the most common types of salivary neoplasms, typically occurs in the superficial lobe of the parotid gland and accounts for 60–70% of all parotid tumors [ 1 ]. Although initially benign, long-standing PA has the potential to transform into malignant pleomorphic adenoma (MPA) and subsequently infiltrate surrounding facial structures, which occurs in 6% of patients [ 2 , 3 ]. MPA can be further classified into three subtypes according to the depth of tumor infiltration beyond the capsule of the previous PA, namely, non-invasive, micro-invasive, and invasive malignant pleomorphic adenoma (IMPA) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some genes have been reported to be abnormally expressed in CXPA rather than PA. Androgen receptor (AR) is overexpressed in CXPA, and its positivity is a useful diagnostic marker for CXPA [ 5 , 6 ]. Both literature and our previous studies have demonstrated that human epidermal growth factor receptor 2 (HER-2, encoded by ERBB-2 gene) amplification promotes CXPA carcinogenesis by enhancing cell proliferation and invasiveness via activating the PI3K/Akt and MAPK/ERK signalling pathways [ 4 , 7 , 8 ]. E-cadherin (E-cad), a well-known adhesion molecule, is down-expressed during carcinogenesis due to the epigenetic and/or genetic alterations in the CDH1 gene [ 9 ].…”
Section: Introductionmentioning
confidence: 99%